IL-27 Inhibits Hyperglycemia and Pancreatic Islet Inflammation Induced by Streptozotocin in Mice - Fujimoto, Hirokazu (American Society for Investigative Pathology, 2011)
Inflammation driven by immune cells and pro-inflammatory cytokines is implicated in pancreatic β-cell injury, leading to the development of diabetes mellitus. IL-27, a cytokine consisting of IL-27p28 and Epstein-Barr virus–induced gene 3 (EBI3), binds a membrane-bound heterodimeric receptor consisting of the IL-27 receptor α chain (WSX-1) and gp130. IL-27 has anti-inflammatory properties that regulate T-cell polarization and cytokine production. We evaluated blood glucose and islet proinsulin concentrations, inflammatory cell infiltration in islets, and expression of IL-1β mRNA in pancreas in wild-type (WT), EBI3(−/−), and WSX-1(−/−) mice treated with streptozotocin (STZ). Hyperglycemia was augmented in EBI3(−/−) and WSX-1(−/−) mice compared with WT mice. Islet proinsulin levels after STZ treatment were lower in EBI3(−/−) and WSX-1(−/−) mice than in WT mice. The infiltration of islets by F4/80(+)CD11c(−)7/4(−) macrophages, CD4(+) T cells, and CD8(+) T cells was increased in EBI3(−/−) and WSX-1(−/−) mice compared with WT mice. The administration of recombinant IL-27, compared with control, decreased the blood glucose level, immune cell infiltration into islets, and IL-1β mRNA expression in the pancreas and increased islet proinsulin levels in WT and EBI3(−/−) mice. Thus, IL-27 inhibits STZ-induced hyperglycemia and pancreatic islet inflammation in mice and represents a potential novel therapeutic approach for β-cell protection in diabetes.